Spiritual Assessment in African-Americans: A Review of Measures of Spirituality Used in Health Research - Lewis, Lisa M. (Journal of religion and health, 2008)
Background A number of instruments have been developed for investigating relationships between spirituality and health, and have been used to assess spirituality in African-Americans. Yet, the cultural appropriateness for African-Americans of these instruments has not been investigated to date. Objectives To evaluate the construct validity and reliability of spirituality measures used in health research from 1982 to 2005. Method Systematic review of the literature. Results Thirty five studies and five measures of spirituality met the inclusion criteria. Most of the spirituality measures were developed in primarily Caucasian-American samples. African-Americans were represented in 71% of the studies (n = 25) using spirituality measures in health research. Distinct cultural attributes of African-American spirituality were omitted in most of the spirituality measures. Two studies were retrieved in which psychometric evaluation was conducted in entirely African-American samples. Discussion Spirituality is a significant cultural experience and belief that influences the health behaviors of African-Americans. The lack of a culturally appropriate measure of African-American spirituality is a major limitation of studies investigating spirituality and health in this population. Development of a culturally appropriate and sensitive measure of spirituality in African-Americans is suggested to strengthen the quality of research in this area.